Parental Awareness to Baby Bottle Tooth Decay in India - Choudhary, Ashish; Kumar, Sumit; Yadav, Pramod Kumar; Pandya, Divya; Mishra, Gaurav (International Journal Of Drug Research And Dental Science, 2022)
Background: Parents’ lifestyles and understanding of oral health have been found to influence the status of their children’s oral health. Baby Bottle Tooth Decay is one of the major causes of pain and infection in the oral cavity of children at an early age and may result in the necessity of tooth extractions before the age of exfoliation of primary teeth leading to other dental problems in the future and costly dental treatment during early ages.Methodology: This was a cross-sectional study carried out at hospitals and malls in Lucknow and Kolkata city. Data was collected using a self-structured questionnaire, from parents of young children about their knowledge pertaining to the occurrence and prevention of baby bottle tooth decay. The minimum sample size of 385 was calculated. However, the study included 705 participants.Results: Knowledge about signs and symptoms and preventive measures of baby bottle tooth decay among their parents were found to be insufficient in this study.Conclusion: Oral health programs focusing on Baby Bottle Tooth Decay should be planned for maternal wards of hospitals and playschools across the country, to enable the new parents, to prevent the occurrence of tooth decay among young children.